Penguatan Sistem Pengamanan Internal Balai Kota Bogor Melalui Pembinaan Wawasan Kebangsaan Dalam Mencegah Ancaman Terorisme - Pranowo, Andityas; Supriyadi, Asep Adang; Sucitra, I Gusti Ngurah Bagus (University of Muhammadiyah Malang, 2023)
This journal aims to discuss the security system for the Bogor City Hall office in dealing with the threat of criminal acts of terrorism. The city of Bogor as a buffer for Jakarta is included in the VIP security ring because it is close to the Bogor Palace. This research method uses qualitative research with a descriptive analysis design. The results of this study conclude that First, physically, strengthening the Internal Security System for the Bogor City Hall Office can be carried out with the following steps; Increase the Risks, Increase the Effort, Reduce the Rewards, Remove Excuses, and Reduce Provocations. Second, efforts to strengthen the Internal Security System for the Bogor City Hall Office through Fostering the National Insight of Employees, fostering national insight for Bogor City Hall employees aims to help them internalize national values, such as love for the motherland, awareness of the importance of national security, and a spirit of unity and unity. Such coaching can help increase their awareness and alertness to suspicious signs and behavior around them.